2013
DOI: 10.1111/j.1540-6520.2012.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship at the Periphery: Exploring Framework Conditions in Core and Peripheral Locations

Abstract: This paper reports the findings of the first academic study in Latin America, and one of the few in any emerging economy, to explore entrepreneurial perceptions and activity in peripheral geographic locations. A survey of experts included 139 respondents from three peripheral regions and two core regions in Chile. A key finding is that those located at the periphery perceived critical entrepreneurial resources and access to markets less favorably than their counterparts at the core, but surprisingly, they perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…We focused on Chile because it is one of the most export‐oriented economy in Latin America (Felzensztein, Brodt, and Gimmon ; Felzensztein et al. ), endowed with a broad range of internationalizing SMEs in the fields of mining, food processing, wine, financial services, and software (Felzensztein, Gimmon, and Aqueveque ). Chile is also a remarkable case in the Latin American region because it was the first economy to liberalize and open its markets to competition, foreign direct investment, and trade during the 1980s.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on Chile because it is one of the most export‐oriented economy in Latin America (Felzensztein, Brodt, and Gimmon ; Felzensztein et al. ), endowed with a broad range of internationalizing SMEs in the fields of mining, food processing, wine, financial services, and software (Felzensztein, Gimmon, and Aqueveque ). Chile is also a remarkable case in the Latin American region because it was the first economy to liberalize and open its markets to competition, foreign direct investment, and trade during the 1980s.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it was found that there is a number of variables which measure peripherality by the types of knowledges routinely used/accessed for decision-making by communities that in turn help identify their resilience-dependence character, something critical to measuring peripherality in many contexts (Felzensztein et al 2013;Nunn and Kumar 2018). The number of mobile phones per capita, while admittedly not adequately capturing global knowledge access/use in Bua, is nevertheless considered key to measuring peripherality; a stage is likely to be reached in the future when novelty/social uses of mobile phones may be replaced by largely practical ones (Walshe et al 2018; Watson and Duffield 2016).…”
Section: Identifying Proxy Measures Of Peripherality For Bua Communitiesmentioning
confidence: 99%
“…Во-первых, вопросы оценки уровня предпринима тельской ак-тивности и детерминант, влияющих на нее на национальном и глобальном уров-нях, по-прежнему занимают важное ме-сто в научных исследованиях (см., напр. : [Bosma, Schutjens, 2011;Hopp, Stephan, 2012;Felzensztein, Gimmon, Aqueveque, 2013;Martínez-Fierro, Biedma-Ferrer, Ruiz-Navarro, 2016] ческих групп и т. п.)…”
Section: использование данных «глобального мониторинга предпринимателunclassified